ANALISIS URGENSI MAGANG JABATAN DALAM SISTEM PENDIDIKAN NOTARIS DI INDONESIA - Dewi Tjandraningsih (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Notarial education in Indonesia demands not only the mastery of legal theory but also practical proficiency in drafting authentic deeds. This research aims to analyze the urgency of office internship as an integral part of the notarial education system in shaping the competence and integrity of prospective notaries. Utilizing a normative legal research method with a statutory approach, this study finds that the office internship serves as a bridge between academic doctrines learned in lectures and the reality of field practice. The results of the analysis indicate that without a structured and standardized internship system, the risk of professional malpractice and violations of the code of ethics increases. Therefore, it is necessary to strengthen regulations regarding the duration, internship curriculum, and supervision from professional organizations to ensure the quality of graduates who are ready to carry out public office professionally. Keywords: Office Internship, Notarial Education, Master of Notary, Competence, Integrity.   Abstrak:  Pendidikan kenotariatan di Indonesia tidak hanya menuntut penguasaan teori hukum, tetapi juga kemahiran praktis dalam pembuatan akta autentik. Penelitian ini bertujuan untuk menganalisis urgensi magang jabatan sebagai bagian integral dari sistem pendidikan notaris dalam membentuk kompetensi dan integritas calon notaris. Menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan, penelitian ini menemukan bahwa magang jabatan berfungsi sebagai jembatan antara doktrin akademis di bangku perkuliahan dengan realitas praktik di lapangan. Hasil analisis menunjukkan bahwa tanpa sistem magang yang terstruktur dan terstandarisasi, risiko terjadinya malpraktik jabatan dan pelanggaran kode etik meningkat. Oleh karena itu, diperlukan penguatan regulasi mengenai durasi, kurikulum magang, serta pengawasan dari organisasi profesi untuk memastikan kualitas lulusan yang siap menjalankan jabatan publik secara profesional. Kata Kunci: Magang Jabatan, Pendidikan Notaris, Magister Kenotariatan, Kompetensi, Integritas.